Home Environment as the Determinant of Educational Aspiration - Kumar Singh*, Pawan (Recent Research in Science and Technology, 2011)
The home and the family provide the first social environment to a child and determine as to what his first attitudes would be towards people and social activities. The kind of child training used in the home has a pronounced influence on later social adjustment. It has been, found that the adolescents who are most popular and most active in the social affairs of their schools and colleges have a warm and friendly feeling towards their families. And on the other hand, there are adolescents in the society who, having depressive home environment in their childhood, are not confident of themselves and do not aspire to achieve anything worthy in life. Therefore the main purpose of the present study is to analyze the psychological causes that account for this social malady and tosuggest so as to create higher educational aspirations among the youth.